2022
DOI: 10.1097/scs.0000000000008569
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Front Mandible Orthokeratinized Odontogenic Cyst – Surgical Management with Preventive Rigid Osteosynthesis

Abstract: Purpose: Cysts and other intrabony lesions can grow asymptomatic until being diagnosed by occasionally done radiologic examination. Missing tooth and malposition of adjacent teeth should induce clinicians to perform X-Ray diagnostic. Methods: A 37-year-old, male patient was admitted with a hopeless tooth 36, to be extracted and replaced with an implant. Clinical examination revealed also missing one of lower incisors and malposition of remaining lower incisors. Cone-beam computed tomography revealed horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Conventional off-the-shelf surgical plates were manually bended according to rapid-prototyped mandible models. Some studies confirmed that prebent plates simplified mandibular reconstruction and improved surgical outcomes compared to freehand surgery ( 27 , 28 ). However, the lack of registered screw holes could unavoidably compromise the precision of surgery, as verified in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Conventional off-the-shelf surgical plates were manually bended according to rapid-prototyped mandible models. Some studies confirmed that prebent plates simplified mandibular reconstruction and improved surgical outcomes compared to freehand surgery ( 27 , 28 ). However, the lack of registered screw holes could unavoidably compromise the precision of surgery, as verified in the present study.…”
Section: Discussionmentioning
confidence: 94%